Oxidative enzymes and vitamin E in ovarian cancer: Insights from a case-control study - Yousif M. AL-dulaimy, Waseem; Sabri Mohammed, Ebtehal; F. Hassuby, Saja; Kadhom, Mohammed (Trends in Immunotherapy, 2023)
Studying vitamin E’s antioxidant capabilities and how they relate to oxidative enzymes in the context of ovarian cancer was the focus of this study. A case-control study was conducted, with 100 women with ovarian cancer serving as cases and 30 women in good health serving as controls. Enzyme-linked immunosorbent assay (ELISA) was used to assess serum levels of trypsin, chymotrypsin, pancreatic-type amylase, and vitamin E, while the dimercaptopropanol tributyrate (BALB) method was used to measure lipase levels. Patients with ovarian cancer were shown to have lower levels of chymotrypsin and lipase and higher levels of trypsin and amylase than controls. The two groups had almost the same vitamin E content. According to these findings, oxidative enzymes may have a role in the progression of ovarian cancer by increasing trypsin and amylase and decreasing chymotrypsin and lipase. Although vitamin E was thought to slow the development of gynecologic malignancies, the study found no such impact. Further research with larger study groups is necessary to obtain more robust results.